MODEL STRATEGI PENGEMBANGAN PARIWISATA BERKELANJUTAN BERBASIS WARISAN BUDAYA DALAM KERANGKA HUKUM PARIWISATA: STUDI MUSEUM KERATON - Anita Anita; Hidayat Andyanto (Fakultas Hukum Universitas Wiraraja, 2026)
Sumenep Regency, one of the regencies on Madura Island with the greatest tourism potential, continues to make efforts to preserve and develop local tourist attractions, one of which is the Sumenep Palace Museum. One of the targets of the Government of Sumenep Regency, which is included annually in the Regional Revenue and Expenditure Budget (APBD), is the development of the Sumenep Palace Museum, referring to Law Number 11 of 2010 concerning Cultural Heritage, which emphasizes that museums are cultural heritage assets that must be preserved and developed. As a derivative regulation, Regional Regulation of Sumenep Regency Number 4 of 2018 concerning the Tourism Development Master Plan (RIPPARKAB) states that cultural heritage objects are part of the tourism destination development pillar and emphasizes that the existence of the Sumenep Palace Museum must be properly maintained and preserved. This study aims to identify sustainable tourism development options based on cultural heritage in Sumenep Regency. The method used in this study includes the collection and analysis of secondary data from various related sources, such as books, journal articles, government reports, and policy documents discussing cultural preservation and sustainable tourism. According to the research findings, Sumenep Regency can create sustainable cultural heritage-based tourism by implementing several important initiatives. First, cooperation between local governments, local communities, and tourism sector stakeholders is required to protect and preserve cultural assets. This collaboration is essential to ensure that tourism can develop without sacrificing existing cultural values. Second, greater emphasis is needed on educating visitors about the importance of local culture so that they not only enjoy but also appreciate and support the preservation of local culture. Third, there is a need for diversification of cultural heritage-based tourism offerings in order to highlight lesser-known local cultural potentials beyond the most famous tourist destinations. By implementing these methods, the cultural heritage-based tourism industry in Sumenep Regency is expected to develop sustainably and provide benefits to local communities in terms of economic, social, and environmental aspects.